Cocktail codex : fundamentals, formulas, and evolutions - Day, Alex; Fauchald, Nick; Kaplan, David (Bartender) (Ten Speed Press, 2018)
From the authors of the best-selling and genre-defining cocktail book Death & Co, Coctail Codex is a comprehensive primer on the craft of mixing drinks that employs the authors' unique "cocktail families" approach to give drink-makers of every level the tools to understand, execute, and improvise both classic and original cocktails--